Saviour siblings - current overview, dilemmas and possible solutions? - Samardžić, Sandra O. (Medicine, law & society, 2019)
In certain cases, when an already born child is affected with a fatal disease and needs transplantation, the only possible solution could be the creation of saviour sibling. Saviour sibling is a term that refers to a child born through a procedure in which an embryo, created in vitro, is being tested in order to determine whether such an embryo could provide stem cells or tissue for an already born, ill child. If the embryo is both, a matching donor and free of the disease, it could be implanted and after the birth of a child, the umbilical cord stem cells or tissue could be used for treatment of a sick sibling. However, this procedure poses a number of dilemmas. This paper aims to give a brief analysis of these issues, to address some of the main concerns and to provide possible solutions for future regulation of this technique.
Keywords: bone marrow; matične celice; medically assisted reproduction; medicina; pravo; right of the child to health; saviour sibling; stem cells; zunajtelesna oploditev